Efektivitas Asas Kerahasiaan Arbitase Indonesia: Antara Perlindungan Informasi dan Tuntutan Transparansi (Lex Mercatoria, 2025)
This article provides an in-depth examination of the effectiveness of the confidentiality principle in Indonesian arbitration amid growing public demands for transparency in dispute resolution. Drawing on a normative legal research design, the study applies statute, conceptual and analytical approaches to role and limitations of confidentiality as mandated by Indonesian Law No. 30 of 1999. The research indentifies theree core findings that is frist, confidentiality remains essential for preseving party autonomy, business privacy, and the efficiency of arbitration, second, insufficient regulatory guidance contributes to inconsistencies the implementation confidentiality, especially in dispute involving State Owned Enterprises (SOEs) and public funds, third, global developments, particulary the UNCITRAL. Transparency Rules and ICSID reforms highlight a shift toward selective transparency for the sake of public accountability. This article contributes to the literature by offering a detailed analytical model of harmonizing these competing interests.Keywords:Arbitration confidentiality, transparency, Indonesian Arbitration, Public accountability, Dispute resolution